Genome of a chronic osteitis‐causing Clostridium tetani. Issue 1 (January 2014) - Fournier, P.‐E.; Levy, P.‐Y.; Million, M.; Croce, O.; Blanc‐Tailleur, C.; Brouqui, P.; Raoult, D.
Abstract We sequenced the genome of a Clostridium tetani strain that caused chronic tibial osteitis without any clinical sign of tetanus in a 26‐year‐old man previously vaccinated against this disease. The genome contained a plasmid that harboured the tetX‐tetR tetanospasmin operon, and was highly similar to that of a tetanus‐causing strain.